ARPANET and its boundary devices: modems, IMPs, and the inter-structuralism of infrastructures. Issue 1 (2nd January 2019) - McKelvey, Fenwick; Driscoll, Kevin
Abstract: Our paper focuses on the Interface Message Processor (IMP), an important device in the history of ARPANET. Designed as the interface between ARPANET nodes and the common carrier telephone system, the IMP actualized the ARPANET as an experimental packet-switching communication system. We conceptualize the IMP as historical boundary object that exposes ARPANET's close relationship to the telephone system. Our analysis offers a novel history of ARPANET as a repurposing of the existing telephone infrastructure. Beyond the historical contribution, this approach has wider implications for the theory of media infrastructures, specifically the "inter-structuralism" of ARPANET and the nature of borders between seemingly disparate social, political, and technological regimes.